GOETHE`S FAUST AND THE QUEST FOR KNOWLEDGE IN THE LIGHT OF UZBEK CULTURAL VALUES (PROBLEMS AND SOLUTIONS OF SCIENTIFIC AND INNOVATIVE RESEARCH, 2025)
This   article explores Johann Wolfgang von Goethe`s Faust  through the combined perspectives  of literature, moral philosophy and cultural studies. The study analyses Faust`s pursuit of knowledge and moral struggle as an educational and ethical journey connecting it with Uzbek cultural values. By comparisons between Goethe`s idea of Bildung (self-cultivation) and Uzbek concepts such as komil inson (perfect person) , the paper argues that both traditions view education as the process of becoming morally and spiritually mature. Through comparative analysis of Goethe`s Faust and writings of Alisher Navoiy and Abdulla Avloniy , this research highlights the shared universal ideal of human self-development through knowledge, conscience and compassion.